Two new deep-sea species of the genus Henricia (Asteroidea: Spinulosida: Echinasteridae) from Japanese waters - Kobayashi, Itaru; Kohtsuka, Hisanori; Fujita, Toshihiko (Zootaxa, 2021)
Two new deep-sea Henricia species, Henricia margarethae n. sp. and Henricia fragilis n. sp. are described from Sagami Bay and the Ogasawara Islands in Japan. The two new species show an affinity with eight congeners in having multiple furrow spines and abactinal papular areas which are larger than surrounding plates. The two species described herein are characterized by the arrangement of abactinal pseudopaxillae, the arrangement of abactinal papulae, the shape and arrangement of abactinal spines, the length of intermarginal and ventrolateral series, and the armament of superomarginal, inferomarginal, and adambulacral plates.